Reaction behaviour of light and heavy components of bio-oil in methanol and in water - Wu, L.; Hu, X.; Wang, Shuai; Hasan, M.; Jiang, S.; Zhang, L.; Li, C. (Elsevier Ltd, 2018)
© 2018 Elsevier Ltd The main components in bio-oil behave differently during the thermal treatment in water or in methanol. Water cannot stabilize the aromatics in bio-oil. Consumption of the aromatics with mono-ring and two fused benzene rings and the formation of the aromatics with three or more fused benzene ring aromatics were observed during the thermal treatment in water. In methanol, the fluorescence intensities of the mono-ring, the aromatics with the two fused ring structures and three-ring aromatics increased. Methanol could stabilize the aromatics and retain them in the reaction medium. The conversion of mono-ring phenolics in thermal treatment of bio-oil in water and their formation in methanol was further confirmed with GC–MS measurement. In addition, it was found that the effects of acetic acid and formic acid on the conversion of the aromatics in bio-oil were negligible. This was probably due to the relative weak acidities of acetic acid and formic acid or the presence of the internal heavy carboxylic acids in bio-oil. However, the conversion of the aromatics in bio-oil was significantly promoted by the strong acids such as Amberlyst 70.